Prevalence and associated factors of suicide among hospitalized schizophrenic patients - Pakapan Woottiluk (2020)
©The Author(s) 2020. BACKGROUND Previous studies found several factors associated with suicide in schizophrenic patients, such as age, sex, education level, history of suicide attempts, psychotic symptoms, social factors, and substance abuse. However, there might be some additional factors that were not considered in previous studies but may be correlated with a greater likelihood of suicide attempts, such as medication and treatment. AIM To investigate the prevalence of suicide attempts and identify the risk of suicidality in hospitalized schizophrenia patients. METHODS This is a cross-sectional study of schizophrenic patients admitted to a psychiatric hospital who were 18 years of age or more. The outcomes and possible suicide risk factors in these patients were collated. The current suicide risk was evaluated using the mini-international neuropsychiatric interview module for suicidality and categorized as none (0 points), mild (1-8 points), moderate (9-16 points), or severe (17 or more points). This study used ordinal logistic regression to assess the association of potential risk factors with the current suicide risk in schizophrenic patients. RESULTS Of 228 hospitalized schizophrenia patients, 214 (93.9%) were included in this study. The majority (79.0%) of patients were males. Females appeared to have a lightly higher suicidality risk than males, with borderline significance. With regard to the current suicide risk assessed with the mini-international neuropsychiatric interview, 172 (80.4%) schizophrenic patients scored zero, 20 (9.4%) had a mild risk, 8 (3.7%) had a moderate risk, and 14 (6.5%) had a severe risk. The total prevalence of current suicide risk in these schizophrenic patients was 19.6%. Based on multivariable ordinal logistic regression analysis with backward elimination, it was found that younger age, a current major depressive episode, receiving fluoxetine or lithium carbonate in the previous month, or a relatively higher Charlson comorbidity index score were all significantly and independently associated with a higher level of suicide risk. CONCLUSION The prevalence rate of suicide attempts in schizophrenia is high. Considering risk factors in routine clinical assessments, environmental manipulations and adequate treatment might prevent or decrease suicide in these patients.